2012
DOI: 10.1007/978-3-642-28729-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Fibrational Induction Meets Effects

Abstract: Abstract. This paper provides several induction rules that can be used to prove properties of effectful data types. Our results are semantic in nature and build upon Hermida and Jacobs' fibrational formulation of induction for polynomial data types and its extension to all inductive data types by Ghani, Johann, and Fumex. An effectful data type µ(T F ) is built from a functor F that describes data, and a monad T that computes effects. Our main contribution is to derive induction rules that are generic over all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Different programming patterns that involve resumptions were discussed by Claessen [14], Kiselyov [28], Harrison [23], and the present authors [38]. Interleaving of data and effects in the algebraic context was also studied by Filinski and Støvring [17], and Atkey et al [10].…”
Section: Related Workmentioning
confidence: 87%
“…Different programming patterns that involve resumptions were discussed by Claessen [14], Kiselyov [28], Harrison [23], and the present authors [38]. Interleaving of data and effects in the algebraic context was also studied by Filinski and Støvring [17], and Atkey et al [10].…”
Section: Related Workmentioning
confidence: 87%
“…A further line of future work lies in deeper investigation of the categorical properties of the category of f -and-m-algebras. In the present work, we constructed the category of f -and-m-algebras and showed that it had initial objects from first principles, while in Atkey et al's previous work (Atkey et al, 2012), this was demonstrated by constructing an adjunction between the category of f -and-m-algebras and the category of ( f • m)-algebras. An anonymous reviewer has pointed out the interesting property that the category of f -and-m-algebras is isomorphic to the category of ((FreeM f ) + m)-EilenbergMoore algebras, showing that the monad coproduct construction in Section 8 has a deeper significance.…”
Section: Future Workmentioning
confidence: 58%
“…The concept of initial f -and-m-algebras is originally due to Filinski and Støvring in the specific setting of Cpo (the category of complete partial orders and continuous functions) (Filinski & Støvring, 2007), and was subsequently extended to a general category-theoretic setting for arbitrary functors f by Atkey, Ghani, Jacobs, and Johann (Atkey et al, 2012). In this article, we aim to introduce the concept of initial f -and-m-algebras to a general functional programming audience and show how they can be used to structure and reason about functional programs in practice, without the heavy category-theoretic prerequisites of Atkey et al's work.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Fibration) 1 For any I ∈ C, Y ∈ E and f : I → pY, there exists X ∈ E above I such that f : X→Y and the following property holds: for any Z ∈ E and g : pZ…”
Section: Definitionmentioning
confidence: 99%